Postmortem interval estimation using the animal model of postmortem gas volume changes. (May 2018) - Iwamoto, Chika; Ohuchida, Kenoki; Okumura, Miki; Usumoto, Yosuke; Kishimoto, Junji; Murata, Masaharu; Ikeda, Noriaki; Hashizume, Makoto
Highlights: The postmortem gas volume were calculated using time-dependent CT images. The volume of postmortem portal venous gas rose exponentially with time after death. The volume of postmortem intestinal gas increased linearly with time after death. Estimation of the postmortem interval by postmortem gas volume changes in the body. Abstract: It is important to estimate the postmortem interval in forensic autopsy. Many methods to estimate the postmortem interval have been reported, and are typically associated with internal examination. However, there are issues such as rejection of autopsy by the family and a lack of forensic doctor in internal examination. Therefore, it is necessary to develop new methods, such as autopsy imaging, that can substitute for internal examination. Here, we first evaluated whether gas volume in the body increased with postmortem interval. Time-dependent X-ray CT imaging of euthanized Crl:CD (SD) rats (n = 3) was performed immediately after euthanasia and at seven subsequent time points up to 168 h (7 days) at 24-hour intervals. The data revealed that gas volume in the body increased in a time-dependent manner. Next, we reconstructed 3D images of isolated gas and calculated the gas volume using Amira software. In all cases, the volume of both portal venous gas and intestinal gas increased in a time-dependent manner. The volume of portal venous gas increased exponentially, while the volume of intestinal gas increased in a linearly with time. These data might be suggested that the postmortem gas volume change is one of indicators for estimating the postmortem interval. In addition, it would be possible to estimate more accurate postmortem interval by combining not only gas volume changes at the above two sites but also gas volume changes of the other sites such as heart cavities, kidney parenchyma, or abdominal aorta.